Lightweight concrete material for traffic engineering arresting and preparation method thereof

By using lightweight concrete materials prepared from cement clinker, gypsum and aluminum-rich phase industrial solid waste, the problem of insufficient energy absorption and durability of existing traffic engineering barrier materials has been solved, and efficient energy absorption and long-life barriers have been achieved. The effect is to improve traffic safety.

CN119330645AActive Publication Date: 2025-01-21CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411292715.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-21
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The existing traffic engineering barrier materials have shortcomings in energy absorption and durability, which are difficult to meet the needs of modern traffic safety.

Method used

A light concrete material is prepared by cement clinse, gypsum, and aluminum -rich industrial solid waste. By regulating the hydration reaction and foam rate, the density and the uniformity of the pores are improved, and its pressure resistance and durability are enhanced.

Benefits of technology

A lightweight concrete material with light texture, stable energy absorption effect, and long service life can effectively meet the needs of traffic engineering blocking and improve the safety of transportation tools and personnel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045082080000061
    Figure BDA0005045082080000061
  • Figure BDA0005045082080000071
    Figure BDA0005045082080000071
  • Figure BDA0005045082080000081
    Figure BDA0005045082080000081
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses a lightweight concrete material for traffic engineering arresting and a preparation method thereof. The lightweight concrete material for traffic engineering arresting, provided by the invention, is prepared from the following components in parts by weight: 171 to 209 parts of cement clinker, 9 to 11 parts of gypsum, 70 to 100 parts of aluminum-rich phase industrial solid waste and 90 to 120 parts of water, the aluminum oxide content of the aluminum-rich phase industrial solid waste is 20-60%, and the fineness is less than or equal to 75 microns; the invention further provides a preparation method of the lightweight concrete material for traffic engineering arresting. The aluminum-rich phase industrial solid waste is subjected to resource utilization and turned into wealth, so that the lightweight concrete material which is light in weight, stable in energy absorption effect and long in service life and is used for traffic engineering blocking is obtained, and the lightweight concrete material can completely meet the blocking requirement of current traffic safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of concrete technology, and in particular to a lightweight concrete material for use in traffic engineering barriers and a preparation method thereof. Background Art

[0002] With the rapid advancement of the strategy of building a strong transportation nation, a large number of transportation projects have been started and constructed. The construction of these major infrastructures has put forward higher requirements for traffic safety. In transportation projects, especially on highways and airport runways, emergency braking and accidental impacts of vehicles and aircraft occasionally occur. The performance of traditional arresting materials in terms of energy absorption and long life can no longer meet the needs of modern traffic safety.

[0003] The main functional material used in the existing airport runway end arresting beds is an ultra-lightweight foam concrete with a crushing and energy-absorbing property. Once an aircraft runs out of the runway and enters the arresting bed, the ultra-lightweight foam concrete will crush under the pressure of the wheels, thereby absorbing the aircraft's kinetic energy, and gradually slowing down the aircraft and eventually stopping it in the arresting bed while ensuring the safety of the aircraft and the people on board.

[0004] However, the existing ultra-lightweight concrete materials still have some shortcomings in the actual application of traffic engineering, such as unsatisfactory energy absorption effect and insufficient durability. Therefore, there is an urgent need for a concrete material with light texture, stable energy absorption effect and long service life to meet the current traffic safety blocking needs. Summary of the invention

[0005] In order to overcome the problems of existing traffic engineering barrier materials such as unsatisfactory energy absorption effect and insufficient durability, the present application provides a lightweight concrete material for traffic engineering barrier and a preparation method thereof.

[0006] The present application provides a lightweight concrete material for traffic engineering blocking, which adopts the following technical solution: A lightweight concrete material for blocking traffic engineering, comprising the following contents in parts by weight: 171-209 parts of cement clinker, 9-11 parts of gypsum, 70-100 parts of aluminum-rich industrial solid waste, 1-4 parts of foaming agent, and 90-120 parts of water; The aluminum-rich industrial solid waste has an aluminum oxide content of 20-60% and a fineness of ≤75 μm.

[0007] The present application uses cement clinker, gypsum and aluminum-rich industrial solid waste to prepare a lightweight concrete material for traffic engineering barriers with light texture, stable energy absorption effect and long service life. Among them, the use of aluminum-rich industrial solid waste, on the one hand, promotes the resource utilization of aluminum-rich industrial solid waste, and on the other hand, reduces the amount of cement clinker; the mechanism of action of the above aluminum-rich industrial solid waste in concrete materials is: aluminum-rich industrial solid waste can regulate C in cement clinker3 The hydration process of S prevents the early hydration reaction of concrete from being too intense, and at the same time coordinates with the foaming rate of the foaming agent to promote the compactness of concrete materials and the uniform and dispersed pores. In addition, the aluminate phase generated by the aluminum element in the aluminum-rich industrial solid waste during the hydration process can fill the pores of the cement matrix, improve the microstructure of the concrete, and greatly enhance the compressive strength and durability of the concrete material.

[0008] Optionally, the aluminum-rich industrial solid waste has the following weight percentage composition: 55μm~75μm aluminum-rich industrial solid waste: 1%~15%; 40μm~55μm aluminum-rich industrial solid waste: 20%~35%; 20μm~40μm aluminum-rich industrial solid waste: 45%~60%; Aluminum-rich industrial solid waste with a particle size less than 20 μm: 1% to 5%.

[0009] In this application, the particle size of aluminum-rich industrial solid waste particles has an impact on the use effect of lightweight concrete materials used for traffic engineering barriers; through experimental research, it is found that by further controlling the particle size and ratio of aluminum-rich industrial solid waste particles within the above range, the obtained lightweight concrete materials used for traffic engineering barriers have good mechanical strength, collapse performance and durability, and can further meet the emergency braking of different types of aircraft and vehicles, ensuring the safety of vehicles and personnel. Among the above-mentioned aluminum-rich industrial solid waste, the fine particles of aluminum-rich industrial solid waste with a particle size of less than 20μm will inhibit C 3 The hydration of S affects the early strength of concrete materials, so its addition should not be too high; the particle size of aluminum-rich industrial solid waste particles of 20μm to 40μm is moderate, and its hydration rate is relatively balanced, which has a great influence on the early strength of concrete materials. 3 The hydration of S is inhibited to a certain extent, but not too significantly. In addition, the aluminum-rich industrial solid waste fine particles of the above particle size can regulate the hydration process of concrete materials to a certain extent, balance the hydration rate and the collapse energy absorption characteristics, and achieve the threshold control of the collapse energy absorption characteristics. The aluminum-rich industrial solid waste particles of 40μm to 55μm have a relatively small specific surface area and a slow hydration rate due to their large particle size, which has an obvious inhibitory effect on C 3 The hydration inhibition effect of S is weak; this part of particles is used as filler in concrete materials to provide certain mechanical support and improve the overall mechanical properties of concrete materials. The coarse particles of aluminum-rich industrial solid waste with a particle size of 55μm to 75μm are larger and have the slowest hydration rate, which has a great influence on C 3The hydration of S is almost unaffected; this part of the particles is mainly used as aggregate filling materials, which play the role of increasing the volume and filling the pores in the concrete material; in addition, the above particles can also dynamically compensate for the decline in shrinkage performance caused by the late aging of the concrete material, thereby extending the service life of the concrete material.

[0010] In some embodiments, the added amount of the aluminum-rich industrial solid waste can be 70-80 parts, 70-90 parts, 70-100 parts, 80-90 parts, 80-100 parts or 90-100 parts.

[0011] In a specific embodiment, the added amount of the aluminum-rich industrial solid waste can also be 70 parts, 80 parts, 90 parts or 100 parts.

[0012] Optionally, the aluminum-rich industrial solid waste has the following weight percentage composition: 55μm~75μm aluminum-rich industrial solid waste: 5%~10%; 40μm~55μm aluminum-rich industrial solid waste: 25%~35%; 20μm~40μm aluminum-rich industrial solid waste: 50%~60%; Aluminum-rich industrial solid waste with a particle size less than 20 μm: 1% to 5%.

[0013] In a specific embodiment, the weight percentage of the aluminum-rich industrial solid waste with a size of 55 μm to 75 μm can be 1%, 5%, 8%, 10% or 15%.

[0014] In a specific embodiment, the weight percentage of the aluminum-rich industrial solid waste with a size of 40 μm to 55 μm can be 20%, 25%, 30% or 35%.

[0015] In a specific embodiment, the weight percentage of the aluminum-rich industrial solid waste with a size of 20 μm to 40 μm can be 45%, 50%, 55% or 60%.

[0016] In a specific embodiment, the weight percentage of the aluminum-rich industrial solid waste with a size less than 20 μm may be 2%, 4% or 5%.

[0017] Optionally, the aluminum-rich industrial solid waste is aluminosilicate industrial solid waste, selected from one or more of coal gangue, shale, kaolin, alum stone, red mud and sludge.

[0018] Optionally, the mineral phase composition of the cement clinker, by weight percentage, includes C 3 S: 25%~58%, C 2 S: 30% to 50%, C 3 A: 2% to 10%, C4 AF: 10%~18%.

[0019] Optionally, the gypsum is selected from one or more of dihydrate gypsum, fluorite, phosphogypsum and desulfurized gypsum.

[0020] Optionally, the lightweight concrete material used for traffic engineering blocking also includes: 2 to 5 parts of foam stabilizer, 1 to 4 parts of accelerating setting agent, 3 to 9 parts of water reducing agent, and 0.5 to 2 parts of fiber.

[0021] Optionally, the foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion; The foaming agent is selected from one or more of rosin-type foaming agents, surfactant-type foaming agents, plant-type foaming agents, animal-type foaming agents, composite foaming agents, ammonium salts, hydrogen peroxide and aluminum powder.

[0022] Optionally, the accelerating setting agent is selected from one or more of alumina clinker accelerating setting agents, water glass accelerating setting agents, aluminate accelerating setting agents and aluminum sulfate accelerating setting agents; The water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; The fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0023] In a second aspect, the present application provides a method for preparing a lightweight concrete material for traffic engineering blocking, comprising the following steps: (1) First, cement clinker, gypsum, aluminum-rich industrial solid waste, foam stabilizer, and fiber are uniformly mixed to obtain a dry mix; (2) Dispersing the water reducer evenly in water and adding it to the dry mix, stirring evenly; then adding the accelerating setting agent, stirring evenly, to obtain slurry A; (3) adding a foaming agent to the slurry A, stirring at a rotation speed of 600-2000 rpm for 5-15 seconds to obtain slurry B; (4) Pour the slurry B into a mold, wait for the foaming height to reach the top of the mold, and then keep it still for 0.5-5 hours; after curing and demolding, a lightweight concrete material for traffic engineering barrier is obtained.

[0024] In some embodiments, the stirring speed in step (3) may be 600-1000 rpm, 600-1500 rpm, 600-2000 rpm, 1000-1500 rpm, 1000-2000 rpm or 1500-2000 rpm.

[0025] In a specific embodiment, the stirring speed in step (3) can also be 600 rpm, 1000 rpm, 1500 rpm or 2000 rpm.

[0026] In summary, this application has the following beneficial effects: 1. This application uses aluminum-rich industrial solid waste to prepare lightweight concrete materials for traffic engineering barriers, thereby realizing the recycling of waste resources and turning waste into treasure. The obtained concrete materials have a light texture, stable energy absorption effect, and a long service life, and can meet the use requirements of traffic engineering barrier materials.

[0027] 2. The present application adopts aluminum-rich industrial solid waste of different particle sizes for compounding, and controls the ratio of each particle size within the following range: aluminum-rich industrial solid waste of 55μm to 75μm: 5% to 10%; aluminum-rich industrial solid waste of 40μm to 55μm: 25% to 35%; aluminum-rich industrial solid waste of 20μm to 40μm: 50% to 60%; aluminum-rich industrial solid waste of less than 20μm: 1% to 5%. The energy absorption effect of the obtained lightweight concrete material is more stable and the anti-freeze durability is better. DETAILED DESCRIPTION

[0028] The present application provides a lightweight concrete material for traffic engineering blocking, comprising the following contents in parts by weight: 171-209 parts of cement clinker, 9-11 parts of gypsum, 70-100 parts of aluminum-rich industrial solid waste, 1-4 parts of foaming agent, 2-5 parts of foam stabilizer, 1-4 parts of accelerator, 3-9 parts of water reducer, 0.5-2 parts of fiber and 90-120 parts of water; the aluminum-rich industrial solid waste has an alumina content of 20-60% and a fineness of ≤75μm.

[0029] The weight percentage composition of the aluminum-rich industrial solid waste is as follows: 1% to 15% of aluminum-rich industrial solid waste of 55 μm to 75 μm; 20% to 35% of aluminum-rich industrial solid waste of 40 μm to 55 μm; 45% to 60% of aluminum-rich industrial solid waste of 20 μm to 40 μm; 1% to 5% of aluminum-rich industrial solid waste of less than 20 μm. Further, the weight percentage composition of the aluminum-rich industrial solid waste is as follows: 5% to 10% of aluminum-rich industrial solid waste of 55 μm to 75 μm; 25% to 35% of aluminum-rich industrial solid waste of 40 μm to 55 μm; 50% to 60% of aluminum-rich industrial solid waste of 20 μm to 40 μm; 1% to 5% of aluminum-rich industrial solid waste of less than 20 μm. The aluminum-rich industrial solid waste is aluminum-silica industrial solid waste, selected from one or more of coal gangue, shale, kaolin, alum stone, red mud and sludge.

[0030] The mineral composition of the cement clinker, by weight percentage, includes C3 S: 25%~58%, C 2 S: 30% to 50%, C 3 A: 2% to 10%, C 4 AF: 10% to 18%. The gypsum is selected from one or more of dihydrate gypsum, fluorite, phosphogypsum and desulfurized gypsum.

[0031] The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizer, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion; the foaming agent is selected from one or more of rosin-type foaming agent, surfactant foaming agent, plant foaming agent, animal foaming agent, composite foaming agent, ammonium salt, hydrogen peroxide and aluminum powder; the accelerator is selected from one or more of alumina clinker accelerator, water glass accelerator, aluminate accelerator and aluminum sulfate accelerator; the water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; the fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0032] The method for preparing the above-mentioned lightweight concrete material for traffic engineering blocking comprises the following steps: (1) First, cement clinker, gypsum, aluminum-rich industrial solid waste, foam stabilizer, and fiber are poured into a mixer and mixed at a speed of 10-600 rpm for 10-60 seconds to obtain a dry mix; (2) Dispersing the water reducer evenly in water and adding it to the dry mix, mixing evenly at a speed of 10-600 rpm; then adding the accelerating setting agent, mixing at a speed of 10-600 rpm for 60-120 seconds, to obtain slurry A; (3) adding a foaming agent to the slurry A, stirring at a rotation speed of 600-2000 rpm for 5-15 seconds to obtain slurry B; (4) Pour the slurry B into a mold, wait for the foaming height to reach the top of the mold, and then stop for 0.5-5 hours; cure in a curing room for 12-72 hours, remove the mold, and continue to cure for 28-40 hours to obtain a lightweight concrete material for traffic engineering blocking.

[0033] In the embodiment of the present application, the mineral composition of cement clinker, by weight percentage, includes C 3 S: 45%, C 2 S: 41%, C 3 A: 6%, C 4AF: 14%; gypsum is industrial-grade dihydrate gypsum, with a content of 90%; aluminum-rich industrial solid waste is red mud, with an alumina content of 45%, and the particle size is ground as needed; the foam stabilizer is hydroxyethyl cellulose ether, purchased from Feicheng Yutian Chemical Co., Ltd.; the water reducer is a polycarboxylic acid-based water reducer, model PC-311; the foaming agent is a rosin-type foaming agent, purchased from Jinan Junde Trading Co., Ltd.; the model of the accelerator is ZY-98; the fiber is polypropylene fiber, purchased from Shandong Honggu New Materials; the raw materials, reagents, solvents, etc. of this application can all be obtained commercially.

[0034] The present application is further described in detail below in conjunction with embodiments and performance testing experiments.

[0035] Examples 1-4 Examples 1-4 each provide a lightweight concrete material for use in traffic engineering barriers.

[0036] The difference between the above embodiments is that the amount of aluminum-rich industrial solid waste added to the lightweight concrete material used for traffic engineering blocking is specifically shown in Table 1 below.

[0037] The method for preparing the lightweight concrete material for traffic engineering blocking of Examples 1-4 comprises the following steps: (1) First, pour 20 kg of cement clinker, 1 kg of dihydrate gypsum, red mud, 0.3 kg of foam stabilizer, and 0.1 kg of fiber into a mixer and mix at a speed of 300 rpm for 10-60 seconds to obtain a dry mix; (2) 0.5 kg of water reducer was evenly dispersed in 10 kg of water and added to the dry mix, and mixed evenly at a speed of 300 rpm; then 0.3 kg of accelerator was added, and mixed at a speed of 300 rpm for 90 seconds to obtain slurry A; (3) adding 0.3 kg of a foaming agent to the slurry A and stirring at a rotation speed of 1000 rpm for 10 seconds to obtain slurry B; (4) Pour the slurry B into a mold, wait for the foaming height to reach the top of the mold, and then leave it alone for 3 hours; cure it in a curing room for 48 hours, remove the mold, and continue curing for 36 hours to obtain a lightweight concrete material for traffic engineering barriers.

[0038] Table 1 Addition amount of aluminum-rich industrial solid waste in the lightweight concrete materials of Examples 1-4 Example Addition amount of aluminum-rich industrial solid waste (kg) 1 7 2 8 3 9 4 10 Example 5-11 Examples 5-11 each provide a lightweight concrete material for use in traffic engineering barriers.

[0039] The difference between the above embodiment and embodiment 2 is that the particle size ratio of aluminum phase industrial solid waste is specifically shown in Table 2 below.

[0040] Table 2 Particle size ratio of aluminum-rich industrial solid waste in lightweight concrete materials of Example 2 and Examples 5-11 Examples 12-14 Examples 12-14 each provide a lightweight concrete material for use in traffic engineering barriers.

[0041] The difference between the above embodiment and embodiment 2 is that the stirring speed in step (3) is specifically shown in Table 3 below.

[0042] Table 3 Stirring speed in step (3) of Example 2 and Examples 12-14 Example Stirring speed in step (3) (rpm) 2 1000 12 600 13 1500 14 2000 Comparative Example 1 Comparative Example 1 provides a lightweight concrete material for use in traffic engineering barriers.

[0043] The difference between the above comparative example and Example 2 is that the amount of aluminum-rich industrial solid waste added to the lightweight concrete material used for traffic engineering blocking is 5 kg.

[0044] Comparative Example 2 Comparative Example 2 provides a lightweight concrete material for use in traffic engineering barriers.

[0045] The difference between the above comparative example and Example 2 is that the amount of aluminum-rich industrial solid waste added to the lightweight concrete material used for traffic engineering blocking is 12 kg.

[0046] Comparative Example 3 Comparative Example 3 provides a lightweight concrete material for use in traffic engineering barriers.

[0047] The difference between the comparative example and Example 2 is that the stirring speed in step (3) is 400 rpm.

[0048] Performance testing The lightweight concrete materials for traffic engineering barriers obtained in Examples 1-14 and Comparative Examples 1-3 were tested for their performance, and the results are shown in Table 4 below.

[0049] (1) The test method for dry density is as follows: refer to JG / T 266-2011 "Foamed Concrete" for testing. Take a group of specimens, test the length, width and height of the specimens respectively, calculate the volume V of each specimen, dry the specimens to constant weight, take them out and weigh the dry mass m of the specimens. 0 The dry density is calculated as follows: Where: ρ 0——Dry density, in kg / m 3 ;m 0 ——mass of the test piece after drying, in g; V——volume of the test piece, in mm 3 .

[0050] (2) The detection method of semi-collapse energy dispersion is: refer to the requirements of MH / T 5111-2015 for detection and calculation; Note: The smaller the semi-collapse energy dispersion, the more stable the energy absorption characteristics of the concrete material.

[0051] (3) The method for testing the collapse strength is as follows: cut a 100mm×100mm×100mm specimen from the test block, dry the specimen to constant weight according to the requirements of MH / T 5111-2015, then place the specimen in a cubic constraint frame and under the compression rod of the universal testing machine, so that the center line of the specimen coincides with the axis of the compression rod, start the universal material testing machine, record the stress and collapse depth during the compression process, and draw the collapse curve of each age. In this application, the average value of the stress data at 15 to 45 mm on the platform section of the collapse curve is taken as the collapse strength.

[0052] (4) The test method for the frost resistance coefficient after 25 freeze-thaw cycles is: test and calculate in accordance with the requirements of MH / T 5111-2015.

[0053] (5) The flame retardant performance grade test method is: test and calculate in accordance with the requirements of GB 8624-2012.

[0054] (6) The testing method for the expected service life is as follows: According to the requirements of MH / T 5111-2015, when the above-mentioned properties of the material meet the standard requirements, it is considered that the expected service life of the material is not less than 20 years.

[0055] Table 4 Performance test results of lightweight concrete obtained from Examples 1-14 and Comparative Examples 1-3 According to the test results in Table 4, the dry density of the lightweight concrete material obtained in Examples 1-14 of the present application is 183-218 kg / m 3 The semi-collapse energy dispersion is 5.2-6.5%, the collapse strength is 0.30-0.35MPa, the antifreeze coefficient after 25 freeze-thaw cycles is 0.8-1.4, the flame retardant grade is A, and the expected service life is not less than 20 years.

[0056] The test results of Examples 1-4 and Comparative Examples 1-2 show that with the increase in the amount of aluminum-rich industrial solid waste added, the dry density and semi-collapse energy dispersion of the obtained lightweight concrete material gradually decrease, and the collapse strength and frost resistance coefficient both show a trend of first increasing and then decreasing; the semi-collapse energy dispersion, collapse strength and frost resistance of the lightweight concrete obtained in Comparative Examples 1-2 are significantly worse than those in Examples 1-4. Therefore, it is explained that the application controls the addition amount of aluminum-rich industrial solid waste within the range of 70-100 parts, and the obtained lightweight concrete material has good performance and can be used for traffic engineering blocking.

[0057] From the test results of Example 2 and Examples 5-11, it can be seen that the semi-collapse energy dispersion of the lightweight concrete materials obtained in Examples 5-6 and Examples 9-11 is 5.2-5.5% (≤5.5), the collapse strength is 0.34-0.35MPa, and the frost resistance coefficient after 25 freeze-thaw cycles is 1.2-1.4; while the semi-collapse energy dispersion of the lightweight concrete materials obtained in Examples 2 and Examples 7-8 is 5.7-6.0% (>5.5), the collapse strength is 0.30-0.32MPa, and the frost resistance coefficient after 25 freeze-thaw cycles is 0.8-1.1. Therefore, it is explained that the present application further controls the weight percentage composition of each particle size in aluminum-rich industrial solid waste within the following range: aluminum-rich industrial solid waste of 55μm to 75μm: 5% to 10%; aluminum-rich industrial solid waste of 40μm to 55μm: 25% to 35%; aluminum-rich industrial solid waste of 20μm to 40μm: 50% to 60%; aluminum-rich industrial solid waste of less than 20μm: 1% to 5%, and the obtained lightweight concrete material has a more stable energy absorption effect and better frost resistance and durability.

[0058] The test results of Example 2, Examples 12-14, and Comparative Example 3 show that in Example 2 and Examples 12-14, the stirring speed in step (3) is controlled within the range of 600-2000 rpm, and the semi-collapse energy dispersion of the obtained lightweight concrete material is 5.6-6.6%, the collapse strength is 0.30-0.32 MPa, and the antifreeze coefficient after 25 freeze-thaw cycles is 0.8-1.0; while in Comparative Example 3, when the stirring speed in step (3) is controlled to 400 rpm, the semi-collapse energy dispersion of the obtained lightweight concrete material is 7.4%, the collapse strength is 0.27 MPa, and the antifreeze coefficient after 25 freeze-thaw cycles is 0.6. Therefore, it is explained that the present application controls the stirring speed in step (3) within the range of 600-2000rpm, and the obtained lightweight concrete material has stable energy absorption effect and good antifreeze durability; further, the semi-collapse energy dispersion of the lightweight concrete material obtained in Example 2 and Example 13 is 5.6-5.8% (≤6.0%), the collapse strength is 0.32MPa, and the antifreeze coefficient after 25 freeze-thaw cycles is 1.0, which means that the present application further controls the stirring speed in step (3) within the range of 1000-1500rpm, and the obtained lightweight concrete material has more stable energy absorption effect and better antifreeze durability.

[0059] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A lightweight concrete material for traffic engineering blocking, characterized in that: The invention comprises the following contents in parts by weight: 171-209 parts of cement clinker, 9-11 parts of gypsum, 70-100 parts of aluminum-rich industrial solid waste, 1-4 parts of foaming agent, and 90-120 parts of water; The aluminum-rich industrial solid waste has an aluminum oxide content of 20-60% and a fineness of ≤75 μm.

2. The lightweight concrete material for traffic engineering blocking according to claim 1 is characterized in that: The weight percentage composition of the aluminum-rich industrial solid waste is as follows: 55μm~75μm aluminum-rich industrial solid waste: 1%~15%; 40μm~55μm aluminum-rich industrial solid waste: 20%~35%; 20μm~40μm aluminum-rich industrial solid waste: 45%~60%; Aluminum-rich industrial solid waste <20μm: 1%~5%.

3. The lightweight concrete material for traffic engineering blocking according to claim 1 is characterized in that: The weight percentage composition of the aluminum-rich industrial solid waste is as follows: 55μm~75μm aluminum-rich industrial solid waste: 5%~10%; 40μm~55μm aluminum-rich industrial solid waste: 25%~35%; 20μm~40μm aluminum-rich industrial solid waste: 50%~60%; Aluminum-rich industrial solid waste <20μm: 1%~5%.

4. The lightweight concrete material for traffic engineering blocking according to claim 1, characterized in that: The aluminum-rich industrial solid waste is aluminum-silica industrial solid waste, selected from one or more of coal gangue, shale, metakaolin, alum stone, red mud and sludge.

5. The lightweight concrete material for traffic engineering blocking according to claim 1, characterized in that: The mineral phase composition of the cement clinker, by weight percentage, includes C3S: 25%-58%, C2S: 30%-50%, C3A: 2%-10%, and C4AF: 10%-18%.

6. The lightweight concrete material for traffic engineering blocking according to claim 1, characterized in that: The gypsum is selected from one or more of dihydrate gypsum, fluorite, phosphogypsum and desulfurized gypsum.

7. The lightweight concrete material for traffic engineering blocking according to any one of claims 1 to 6, characterized in that: The lightweight concrete material used for traffic engineering blocking also includes: 2-5 parts of foam stabilizer, 1-4 parts of accelerating setting agent, 3-9 parts of water reducing agent, and 0.5-2 parts of fiber.

8. The lightweight concrete material for traffic engineering blocking according to claim 7, characterized in that: The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizer, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion; The foaming agent is selected from one or more of rosin-type foaming agents, surfactant-type foaming agents, plant-type foaming agents, animal-type foaming agents, composite foaming agents, ammonium salts, hydrogen peroxide and aluminum powder.

9. The lightweight concrete material for traffic engineering blocking according to claim 7, characterized in that: The accelerating setting agent is selected from one or more of alumina clinker accelerating setting agents, water glass accelerating setting agents, aluminate accelerating setting agents and aluminum sulfate accelerating setting agents; The water reducer is selected from one or more of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer; The fiber is selected from one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

10. The method for preparing a lightweight concrete material for traffic engineering blocking according to any one of claims 7 to 9, characterized in that: The following steps are involved: (1) First, cement clinker, gypsum, aluminum-rich industrial solid waste, foam stabilizer, and fiber are mixed evenly to obtain a dry mix; (2) Disperse the water reducer evenly in water and add it to the dry mix, stirring evenly; then add the accelerating setting agent and stir evenly to obtain slurry A; (3) adding a foaming agent to the slurry A, stirring at a speed of 600-2000 rpm for 5-15 seconds to obtain slurry B; (4) Pour the slurry B into a mold, wait for the foaming height to reach the top of the mold, and then keep it still for 0.5-5 hours; after curing and demolding, a lightweight concrete material for traffic engineering barrier is obtained.

Citation Information

Patent Citations

  • Novel aircraft cross-border arresting material and preparation technology thereof

    CN106278362A

  • Airfield runway specific material blocking system, preparation method thereof and testing device

    CN110078437A

  • Light energy-saving material for airport runway block system and preparation method thereof

    CN110510931A

  • Solid waste-based foam light soil as well as preparation method and application thereof

    CN117303839A

  • Ultra-lightweight concrete and use thereof

    FR2957073A1